2008
DOI: 10.1111/j.1365-294x.2008.04014.x
|View full text |Cite
|
Sign up to set email alerts
|

Invasion genetics of the Eurasian round goby in North America: tracing sources and spread patterns

Abstract: The Eurasian round goby Neogobius melanostomus (Apollonia melanostoma) invaded the North American Great Lakes in 1990 through ballast water, spread rapidly, and now is widely distributed and moving through adjacent tributaries. We analyse its genetic diversity and divergence patterns among 25 North American (N = 744) and 22 Eurasian (N = 414) locations using mitochondrial DNA cytochrome b gene sequences and seven nuclear microsatellite loci in order to: (i) identify the invasion's founding source(s), (ii) test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
108
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 110 publications
(119 citation statements)
references
References 103 publications
(137 reference statements)
11
108
0
Order By: Relevance
“…Given the hermaphrodite mode of reproduction in M. leidyi, our findings underline the importance of reproductive strategies for invasion success, despite losses in genetic diversity (Roman & Darling 2007). Finally, our study contributes to the growing evidence that not all invasions need to be accompanied by losses of genetic diversity (Rius et al 2008, Brown & Stepien 2009) and successful invasions can vary broadly in their degree of genetic diversity (Darling et al 2008). …”
Section: Southern Invasion and Spread Into The Mediterranean Seasupporting
confidence: 60%
“…Given the hermaphrodite mode of reproduction in M. leidyi, our findings underline the importance of reproductive strategies for invasion success, despite losses in genetic diversity (Roman & Darling 2007). Finally, our study contributes to the growing evidence that not all invasions need to be accompanied by losses of genetic diversity (Rius et al 2008, Brown & Stepien 2009) and successful invasions can vary broadly in their degree of genetic diversity (Darling et al 2008). …”
Section: Southern Invasion and Spread Into The Mediterranean Seasupporting
confidence: 60%
“…If the high neutral genetic diversity corresponds to adaptive genetic variation in coding loci, then the expansion of D. rostriformis bugensis may be coupled to enhanced adaptability (Zayed and Whitfield 2008). Similar large-scale introductions, high genetic diversity and no founder effects have been found for D. rostriformis bugensis and D. polymorpha in the Great Lakes (Hebert et al 1989;Marsden et al 1995;Stepien et al 2002Stepien et al , 2005 and in Ireland (Astanei et al 2005) and have been reported for Ponto-Caspian invasive fish species in North America (Stepien et al 1998(Stepien et al , 2005Stepien and Tumeo 2006;Brown and Stepien 2009).…”
Section: Discussionmentioning
confidence: 88%
“…Selectively neutral molecular markers can serve as a proxy for estimating quantitative genetic variation in phenotypic traits that underlies adaptive evolution (Merila and Crnokrak 2001;Reed and Frankham 2001;Chun et al 2009). Population genetic data also are useful for elucidating the number and sources of an introduction (Stepien et al 2005;Rosenthal et al 2008;Brown and Stepien 2009), as well as determining whether changes occur during the time course of its establishment and spread (Andreakis et al 2009;Henry et al 2009). Such information can aid control efforts.…”
Section: Role Of Geneticsmentioning
confidence: 99%
“…Spread of dreissenid ''mats'' on the lake floors-where they host an associated community of plants and invertebrates in their shells and interstices-has further increased benthification, markedly changing the ecosystem (Zhu et al 2006;Hebert et al 2009;Stewart et al 2009). Dreissenids likely facilitated the invasion of the round goby Neogobius melanostomus (Vanderploeg et al 2002), their natural predator that became established throughout the Great Lakes, whose populations have high genetic diversity and show no founder effect (Stepien and Tumeo 2006;Brown and Stepien 2009).…”
Section: Introductionmentioning
confidence: 99%